Percepção e atitude dos profissionais de saúde frente à violência intrafamiliar - Wakayama, Bruno [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Domestic violence has increased remarkably in Brazil routine and consequently, it has been considered as a public health problem. This kind of violence is characterized as physical, psychological, economic, sexual or omission, being committed by one of familiar member, in or out of local life. The constant targets of these aggressions are vulnerable groups that due to this kind of violence, they have personality compromised, and psychological damages closing a cycle for violent behaviors. To notify it is a way to block the violent relations through support to victims at professional and institutional levels. Notification is a charge of health professional front suspect and/or diagnosis of violence. However, for health professionals the violence practice is perceived as frail and tenuous because of their lack of knowledge, unpreparedness and fears. The aim of this study was to evaluate the perception of health professional of public health services regarding to violence and difficulties to notify it. Deal with a descriptive, cross-sectional cohort study with a qualitative and quantitative profile. Statistical analysis will be made applying Chi-squared and Fisher's Tests for quantitative sample and Bardin's content analysis for qualitative data. Were part of this study, health professionals from the public service in two cities in the State of São Paulo. It was used a semi-structured instrument composed by open and closed questions. According to the response, we verified the professional unpreparedness of most health professionals in the diagnosis of violence, as well as existing shelter for victims means. Ignorance of the notification form and the professional duty to notify such cases, as well as the fears and fears intevir in cases violence, suggests the need for professional training on the subject, and the development of strategies to facilitate the process of notification by health professionals

A violência intrafamiliar tem se caracterizado de maneira alarmante na realidade brasileira, portanto, sendo considerado um problema de Saúde Publica. É caracterizada como uma agressão física, psicológica, econômica, sexual ou omissão que é acometido por um dos membros de uma família, dentro ou fora do seu espaço físico de vivência. Os alvos constantes dessas agressões são grupos vulneráveis, que a mercê dessa violência gratuita, acarretam no comprometimento da personalidade, sequelas psicológicas, à vista disto, formando um ciclo para pratica de comportamentos violentos. O ato de notificar é uma medida de interromper as relações de violência através de amparo a essas vitimas a nível profissional e institucional. A notificação é de encargo do profissional da saúde perante a suspeita e ou diagnóstico de violência. Entretanto, a prática dessa ação é percebida como frágil e tênue pelos profissionais, por falta de conhecimento, despreparo e receios. O objetivo do estudo foi avaliar a percepção dos profissionais de saúde do serviço público sobre o tema violência e as dificuldades no processo de notificação. Tratou-se de um estudo descritivo de corte transversal quati-qualitativo. Fizeram parte do estudo profissionais da saúde do serviço publico de dois municípios do estado de São Paulo, um de pequeno e outra de médio porte. Foi utilizado para coleta um inquérito semi-estruturado com questões abertas e fechadas. Para as análises estatísticas serão utilizadas o teste qui-quadrado e e Fisher para amostra quantitativa e a análise de conteúdo por BARDIN para a analise qualitativa. De acordo com as resposta, foi verificado o despreparo profissional da maioria dos profissionais da saúde no diagnóstico de violência, bem como os meios existentes para amparo as vitimas. O desconhecimento da ficha de notificação, o dever...
Keywords: Violência; Saúde pública; Epidemiologia; Políticas públicas; Violence